Pengaruh Kualitas Layanan dan Variasi Produk serta Persepsi Harga Terhadap Kepuasan Konsumen Solaria Big Mall Samarinda - Aliyah, Yusfika; Sampeliling, Alexander (Jejak digital: Jurnal Ilmiah Multidisiplin, 2026)
This study aims to examine and analyze the effect of service quality, product variety, and price perception on consumer satisfaction at Solaria Big Mall Samarinda.  The population in this study includes all consumers who visited at Solaria Big Mall Samarinda. The sampling technique used non-probability sampling with a purposive sampling approach, obtaining 120 respondents who met the criteria of being 17 years old or older and residing in Samarinda. Data collection was conducted by distributing online questionnaires via Google Forms measured with a Likert scale. The data analysis technique applied was multiple linear regression analysis using SPSS 26 software. The results of the multiple linear regression analysis generated the equation Y = 0.289 + 0.334X1 + 0.175X2 + 0.415X3. The F-test results showed that service quality, product variety, and price perception have a  effect on consumer satisfaction with an F-count value of 50.261 and a significance level of 0.000. Partially, the t-test proved that service quality has a positive  effect on consumer satisfaction. Price perception also has a positive and significant effect on consumer satisfaction and stands as the most dominant variable affecting satisfaction. Conversely, product variety has a positive effect, but the strength of that effect is not yet statistically insignificant effect on consumer satisfaction at Solaria Big Mall Samarinda, as consumers tend to  prioritize taste consistency and the quality of flagship items over the abundance of menu choices. The capacity of independent variables to explain consumer satisfaction (R Square) is 56.7%, while the remaining 43.3% is explained by other variables outside this research model.